Transforming Chemistry Learning through the Development of Higher Order Thinking Based on Revised Bloom's Taxonomy: A Systematic Review - Putri, Annisa Khairani; Fahrunisa, Allika Haya; Evriliani, Agnes Suci; Volosa, Erin; Nahadi, Nahadi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Education is a structured and systematic learning process that aims to improve the knowledge, skills, attitudes and values needed to build a successful career and life. Through education we can produce human resources who are competent and resilient in facing a complex future. The way to produce competent human resources is to improve students' Higher Level Thinking Skills in the learning process. The application of the Revised Bloom's Taxonomy in learning is able to improve students' high-level thinking skills because the revised Bloom's Taxonomy has levels of cognitive abilities starting from low level (LOTS) to high level (HOTS). To find out feedback and student learning outcomes, look at the results of the assessment process after learning. These results can be a reference and even input for teachers to always develop the critical thinking skills learning process. Thus, this article aims to present knowledge information regarding the development of learning high-level thinking skills in chemistry subjects based on the revised Bloom's taxonomy which refers to student assessment.